Pengaruh Religiusitas Terhadap Gaya Hidup Konsumen Muslim Di Ponorogo - Sumbu Latim Miatun; Lukman Santoso (LPMP Imperium, 2020)
Purpose- This study aims to determine the effect of religiosity on the lifestyles of Muslim consumers Artomoro stores in Ponorogo. Methods- A total of 97 Muslim consumer respondents at the Artomoro store in Ponorogo were sampled. Sampling uses the Purposive Sampling method, then the data is processed using SPSS 16.0. Data collection instruments using a questionnaire with a Likert scale that has been tested and has met the requirements of validity and reliability. The analytical method used to determine the magnitude of the effect is a simple linear regression. Findings- The results of the study concluded that there is a positive and significant influence between religiosity on lifestyle. The results showed that there was a significant influence of religiosity on the lifestyle of Muslim consumers in Artomoro shops in Ponorogo by 9.9% and the remaining 90.1% was influenced by other variables not discussed in this study.